Masculinidades nos desenhos animados : as representações De Johnny Bravo e Steven Universo - Kropidloski, Ícaro Matos (2023)
Through this research, we propose an overview of masculinities in children's cartoons and to understand different imaginaries that populate the being man/masculine (the hegemonic man and the counter-hegemonic man) in Western societies. Our idea of masculinities as an area of academic production comes from the Feminist Movement, which reconsiders the idea of man as a universal human being and places him as an object of research. When we talk about gender and imaginaries, we turn to authors such as Butler (2018, 2021), Connel (1995) Maffesoli (2012) and others. The chosen studio was Cartoon Network and the characters that constitute our objects of study are Johnny Bravo and Steven Universe. We analyzed five random episodes from different cultural and sociopolitical contexts of each character. In this way, we access these different masculinities, represented in the characters, which divide attention and populate minds and hearts. There is a dispute of imaginaries, a debate between a hegemonic ideal and a queer and fluid contemporary one. We understand here who the characters are and where they come from, the aspects that concern the production